LAPAROSCOPIC LIVING DONOR NEPHRECTOMY WITH TRANSVAGINAL GRAFT EXTRACTION - D. V. Perlin; I. V. Aleksandrov; A. D. Sapojnikov; A. Y. Nikolaev (Вестник трансплантологии и искусственных органов)
This article describes the first experience of laparoscopic donor nephrectomy with transvaginal kidney graft extraction. The surgical technique and long-term results are shown. The advantage of surgery is the absence of pain in the early postoperative period and good cosmetic results compared to standard laparoscopic nephrectomy. However, candidates for this operation should be carefully selected to maintain donor safety and graft viability.